Evaluation of eye melanoma treatments in rabbits: A systematic review. (April 2022) - Guimarães, Tarcísio Guerra; Marto, Carlos Miguel; Cardoso, Karla Menezes; Alexandre, Nuno; Botelho, Maria Filomena; Laranjo, Mafalda
Melanomas are the most common cancer of the eye in canines, felines and humans. The treatment approaches vary, since no gold standard exists. Therefore, this systematic review aimed to compare the treatment modalities in ocular melanoma in rabbits. Medline/PubMed, Cochrane Library, Web of Science and Embase were searched for articles published until 21 April 2021 in English, Portuguese or Spanish, reporting animal studies evaluating photodynamic therapy (PDT), laser, radiotherapy or surgical excision. Twenty-seven articles were included for the qualitative synthesis, with publication dates from 1970 to 2018. Of the selected studies, 19 used PDT, six used radiotherapy and two used laser as treatment. No studies regarding surgical therapy that met the inclusion criteria were obtained. The tumour therapy results were evaluated in a heterogeneous manner for different periods and various methods, including microscopy, angiographic, histological examination, fundoscopy, ultrasound exam and electroretinogram. The treatment modalities analysed successfully treated the ocular melanoma, with tumour necrosis being commonly observed. Despite the therapeutic efficacy shown, side effects have been reported for all the therapies. The studies showed high heterogeneity, and therefore, in the future, new studies should be carried out to increase knowledge about ocular melanoma treatment. The analysed therapies can be used successfully in the treatment of ocular melanoma, with more conservative options such as PDT presenting great potential.